The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/002214650804900102
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and Hunger

Abstract: We employ data from the National Survey of Homeless Assistance Providers and Clients to examine the character and correlates of hunger among homeless people. Our analysis, couched in an adaptation framework, finds more support for the differentiation hypothesis than for the leveling hypothesis: Complex patterns of food insecurity exist at the individual level, and they vary with the resources available (e.g., higher monthly income, regular shelter use) and obstacles faced (e.g., alcohol, drug, and physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 34 publications
5
69
1
2
Order By: Relevance
“…This finding is concordant with prior work demonstrating a high burden of food insecurity among chronically homeless individuals, further disputing the notion that the accumulated "street wisdom" of entrenched homelessness might endow a protective effect against lacking food because of increased knowledge about how to acquire it. 4 Instead, the clustering of food, shelter, and safety concerns documented in this study suggests that difficulty in meeting one basic subsistence need predicts difficulties with others.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This finding is concordant with prior work demonstrating a high burden of food insecurity among chronically homeless individuals, further disputing the notion that the accumulated "street wisdom" of entrenched homelessness might endow a protective effect against lacking food because of increased knowledge about how to acquire it. 4 Instead, the clustering of food, shelter, and safety concerns documented in this study suggests that difficulty in meeting one basic subsistence need predicts difficulties with others.…”
Section: Discussionmentioning
confidence: 59%
“…Competing demands for food are common among homeless individuals and may influence health care utilization patterns. [4][5][6] Homeless people who do not get enough food to eat may postpone or forego needed medical care until later stages of illness, [6][7][8][9] choose to buy food over medications, [10][11][12] or have difficulty managing health conditions and adhering to treatment plans. [13][14][15] In some cases, homeless people may use health services in order to get food.…”
Section: Introductionmentioning
confidence: 99%
“…Using a sample of households in Los Angeles County, Furness et al (2004) found that a history of homelessness is associated with food insecurity. Lee and Greif (2008) used data from the National Survey of Homeless Assistance Providers and Clients (NSHAPC) and found that homeless individuals were at higher risk of experiencing food insecurity. Some limitations of these studies are their cross-sectional design and the possibility that the findings could be due to selection.…”
Section: Introductionmentioning
confidence: 99%
“…Homeless adults represent a marginalized, neglected segment of the population and are known to experience poorer physical health than the general population. 9,10 Because adults who are chronically homeless lack a stable, secure residence and often cannot afford regular, healthy meals, [11][12][13] they are presumed to be underweight. However, this assumption has not been empirically examined, and there is evidence to suggest there may be an obesity problem among the homeless.…”
mentioning
confidence: 99%